Micro X‐ray diffraction and elemental study on Al‐tobermorite formation in aged modern concrete. Issue 11 (7th July 2022) - Aili, Abudushalamu; Maruyama, Ippei; Geng, Guoqing; Umeki, Shota; Sumitani, Kazushi; Sawada, Shohei; Ueda, Shinya; Umeki, Yoshito
Abstract: In modern Portland cement, calcium aluminum silicate hydrates (C‐A‐S‐H) do not generally form crystalline Al‐tobermorite. In this study, to identify the mechanism of Al‐tobermorite formation, synchrotron micro X‐ray diffraction and field‐emission scanning electron microscopy‐based energy‐dispersive X‐ray spectroscopy (EDS) investigations were performed on a slice of a thick concrete wall in a nuclear power plant, where the presence of Al‐tobermorite was previously confirmed. Rietveld analysis of the diffraction diagrams obtained from the 2D diffraction patterns showed that Al‐tobermorite was formed almost everywhere in the cement paste near sandstone aggregate and that Al‐tobermorite platelets were distributed across most of the cement paste area in a random orientation. The basal spacing d ‐value of Al‐tobermorite was identical and equal to 11.39 Å. The ratio plots from the EDS maps indicated that the chemical composition of the mixture of Al‐tobermorite and C‐A‐S‐H was almost homogeneous all around the cement paste. The Al‐tobermorite in this concrete is probably formed via a dissolution–precipitation process. From the random orientation even next to the surface of aggregate, we infer that the Al‐tobermorite formation does not need the surface of aggregate to precipitate.